One-loop integrability with shifting masses - Matheus Fabri; Davide Polvara (Journal of High Energy Physics)
Abstract We investigate the perturbative integrability of two-dimensional massive quantum field theories with polynomial-like interactions and show that any theory of such class which is purely elastic at the tree level is also purely elastic at one loop. To preserve the elasticity, the physical renormalized masses of the theory must differ from the classical ones by quantum corrections carried by one-loop bubble diagrams. After the masses are corrected in this manner we show that one-loop inelastic processes vanish and integrability is preserved under one-loop effects. Relying on this fact we show that the closed expression for one-loop S-matrices in terms of tree S-matrices obtained in [1] extends to models that do not preserve the mass ratios at one loop. We test our results on the full class of nonsimply-laced affine Toda theories and find exact match with the S-matrices bootstrapped in the past.